The Effect of Workplace Democracy and Compensation on Employee Retention: The Mediating Role of Job Satisfaction among Coffee Shop Employees in Pangkalpinang City (International Journal of Economics and Management Research, 2026)
This study aims to analyze the influence of workplace democracy and compensation on employee retention in coffee shop employees in Pangkalpinang City, with job satisfaction as a mediating variable. Using a quantitative approach with a comparative causal design, data was collected through an online survey distributed to employees working in the local coffee shop industry. This study examines the direct influence of workplace democracy and compensation on job satisfaction and employee retention, while assessing the mediating role of job satisfaction in these relationships. The results of the study show that workplace democracy and compensation have a positive and significant influence on job satisfaction and employee retention. In addition, job satisfaction has been shown to mediate the relationship between workplace democracy and compensation and employee retention, thereby improving understanding of the psychological mechanisms that drive workforce sustainability in the creative small business sector. These findings contribute to the development of literature on democratic participation and compensation practices in the context of small businesses, and provide practical implications for business owners and policymakers to design more equitable, participatory, and sustainable employment strategies to improve employee stability and loyalty in the coffee shop industry.